2021
DOI: 10.1002/jocb.521
|View full text |Cite
|
Sign up to set email alerts
|

Creativity Outside School: The Influence of Family Background, Perceived Parenting, and After‐school Activity on Creativity

Abstract: The present research involved two studies that investigated the creativity development of Chinese children and young adolescents (9-14 years old). It was hypothesized that family socio-economic status (SES), perceived parenting (e.g., parental autonomy support, involvement, and overcontrol), and after-school activities contribute to the development of creativity. Study 1 showed that self-rated creativity (mini-c) was positively associated with children's perceived parenting and SES, whereas expert-rated creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Yang et al (2020) used data analysis to find that the socioeconomic status of college students’ families predicted creativity. Liang et al (2021) also found that respondents’ self-rated creativity is positively related to family socioeconomic status in an investigation among Chinese adolescents aged 9–14. In addition, Zhang et al (2020) argued that learners’ gender also affects creativity; specifically, boys outperform girls in terms of originality of creativity, but girls outperform boys in terms of abstraction.…”
Section: Introductionmentioning
confidence: 86%
“…Similarly, Yang et al (2020) used data analysis to find that the socioeconomic status of college students’ families predicted creativity. Liang et al (2021) also found that respondents’ self-rated creativity is positively related to family socioeconomic status in an investigation among Chinese adolescents aged 9–14. In addition, Zhang et al (2020) argued that learners’ gender also affects creativity; specifically, boys outperform girls in terms of originality of creativity, but girls outperform boys in terms of abstraction.…”
Section: Introductionmentioning
confidence: 86%
“…As a result, a higher level of education (self or parental) may result in a higher exposure to diverse ideas and enhancing DT performance, whereas a higher income may be associated with a greater level of creative activity and behavior. Some studies focused on one of these SES indicators (Chang, Hsu, Shih, & Chen, 2014; Ivcevic & Kaufman, 2013) while others proceeded without specifying the SES dimensions (Liang, Niu, Cheng, & Qin, 2022). Additional studies used psychometric instruments of SES (Seymour, 1975; Xu & Pang, 2019).…”
Section: Socio‐economic Statusmentioning
confidence: 99%
“…Promoting creativity in general and in the classroom in particular, requires a better understanding of why people often decide not to create. Such reasons and obstacles are of a different nature, ranging from a low level of creative interests and abilities (Benedek et al, 2020), to a difficult position in social strata (Castillo-Vergara et al, 2018), to a low value ascribed to creativity in a family (Liang et al, 2021). Yet, what seems essential is the motivational sphere of self-perception (Karwowski & Kaufman, 2017).…”
Section: Introductionmentioning
confidence: 99%